Incidencia de infecciones nosocomiales en el hospital universitario del cantón guayaquil, periodo enero - abril 2024. - Capito Guamán, Segundo Rolando (2024)
The present study addresses the incidence of nosocomial infections and their contributing risk factors in neonates hospitalized in the neonatal intensive care unit. Therefore, the main objective is to determine the incidence of nosocomial infections and their contributing risk factors in neonates in the neonatal intensive care unit of the Hospital Universitario del Cantón Guayaquil. A descriptive, cross-sectional and retrospective study was carried out using two previously validated instruments in a sample of 7 nursing professionals and 32 neonates hospitalized in the Isolated NICU area. The results indicated that the incidence of infection associated with health care was 12.5%, including pneumonia associated with mechanical ventilation and central or percutaneous catheterization, these complications are mainly due to risk factors such as prematurity, low birth weight, respiratory distress syndrome and the most frequent invasive procedures, such as central venous catheter placement, intubation or prolonged use of mechanical ventilation. On the other hand, it could also be related to poor adherence to the hygiene protocols established by the World Health Organization, such as the five moments of hand washing, especially in the handling of invasive devices. Frequent hand washing and the application of the five moments is crucial to reduce and prevent infections in neonate